A complete linkage disequilibrium in a haplotype of three SNPs in Fat Mass and Obesity associated (FTO) gene was strongly associated with anthropometric indices after controlling for calorie intake and physical activity - Naser Kalantari; Nastaran Keshavarz Mohammadi; Pantea Izadi; Maryam Gholamalizadeh; Saeid Doaei; Hassan Eini-Zinab; Tuire Salonurmi; Shahram Rafieifar; Reza Janipoor; Ghasem Azizi Tabesh (BMC, 2018)
Abstract Background The underlying mechanism of the effect of FTO genotype on body mass index (BMI) and body composition is unknown. The objective of the study was to investigate the association of FTO gene polymorphisms with anthropometric indices in adolescent boys after adjustments for dietary intake and physical activity. Methods In this school-based study, we enrolled 123 male adolescents without extra weight and 110 male adolescents with body mass index (BMI) higher than + 1 Z-score. The DNA samples were genotyped for the FTO gene polymorphisms by DNA Sequencing. BMI and body composition were assessed using bioelectrical impedance analyzer scale. Association of the FTO polymorphisms with Weight, height, BMI, body fat percent and skeletal muscle percent were investigated. Data on potential confounders (calorie intake and physical activity) were collected through the use of pre-tested questionnaires. Results Adolescents with higher BMI and body fat percent and lower skeletal muscle percent were more likely to have a newly found haplotype of rs9930506, rs9930501 & rs9932754 (GGT) in the first intron of the FTO with complete linkage disequilibrium (LD) compared with those with the lower BMI (6.15;2.28-16.63), body fat percent (9.54;0.92-47.44) and higher skeletal muscle percent (9.26;1.85-46.38). This association was not changed after controlling for age. Additional adjustments for calorie intake and physical activity did not alter the association. Conclusions A haplotype in the first intron of the FTO gene had a strong association with obesity indices in adolescent boys after adjustments for calorie intake and physical activity. It's suggested that the FTO genotype exert its effects on adolescents' anthropometric indices as haplotype and through mechanisms other than changes in calorie intake and expenditure. Trial registration This paper reports the first phase of a comprehensive interventional study (Interactions of Genetics, lifestyle and anthropometrics study or IGLA study) and is retrospectively registered in the Iranian Registry of Clinical Trials as IRCT2016020925699N2. Date registered: April 24, 2016. (http://www.irct.ir/searchresult.php?id=25699&number=2).